The Impact of Business Environment Institutions on the Economic Development of Cities in the Silesian Voivodeship - Rykała, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
The subject of the article focuses on issues related to business environment institutions, including the identification of their impact on the economic development of cities. The aim of the article is to search for urban development trends in the context of the presence of business environment infrastructure, distinguishing cities characterized by similar development dynamics in selected socio economic dimensions. The study consists of four parts. In the first one, an attempt was made to reflect on the issue of economic development of cities by analyzing selected development concepts. The second part presents the issue of Business Environment Institutions from a theoretical perspective. The third part presents the methodological assumptions and research results regarding the impact of Business Environment Institutions on the economic development of cities in the Silesian Voivodeship. The last part contains conclusions and a summary.